2022
DOI: 10.1007/s10921-022-00903-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved Tafel-Based Potentiostatic Approach for Corrosion Rate Monitoring of Reinforcing Steel

Abstract: Potential step voltammetry (PSV) was introduced in earlier works as an advantageous alternative to traditional methods for measuring corrosion rate in reinforced concrete. The present study aims to improve PSV to maximize its applicability in corrosion rate monitoring, that is, beyond the narrowly-defined steel–concrete systems in which was initially validated. It was therefore identified necessary to address the most suitable PSV pulse amplitudes to accurately obtain the Tafel lines and, therefore, corrosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The calculated values of the cathode and anode slope were all high. However, for the bare SS support, the cathodic slope was significantly higher than the anodic one, indicating a cathodic reduction detrimental to the anodic oxidation [58][59][60]. In the case of SS/Ti(N,O) coatings, the slopes were quite similar, such that it may be concluded that the hydrogen evolution and metal dissolution were almost in equilibrium [61].…”
Section: Electrochemical Evaluation-tafel Plotsmentioning
confidence: 99%
“…The calculated values of the cathode and anode slope were all high. However, for the bare SS support, the cathodic slope was significantly higher than the anodic one, indicating a cathodic reduction detrimental to the anodic oxidation [58][59][60]. In the case of SS/Ti(N,O) coatings, the slopes were quite similar, such that it may be concluded that the hydrogen evolution and metal dissolution were almost in equilibrium [61].…”
Section: Electrochemical Evaluation-tafel Plotsmentioning
confidence: 99%
“…During the exposure period, the corrosion rate was periodically measured in each rebar using the potentiostatic step voltammetry (PSV) technique. This technique has been described and validated in previous works [127][128][129][130]. It allows for rebar corrosion analysis by studying the response of steel to potentiostatic-type disturbance.…”
Section: Corrosion Ratementioning
confidence: 99%
“…These include the following: Due to the electrochemical nature of the corrosion processes that occur in reinforced concrete structures, several methods are used for diagnostic tests. They determine the probability of corrosion in reinforcement (that is, measurement of stationary potential and resistivity of concrete cover) or the rate of corrosion progress in reinforcement (that is, polarisation method) [3,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%